The problem of Lenin’s self-identification and the Russian revolution - Gataullina, I.A. (Opción, 2019)
The study aims to investigate the problem of Lenin’s self-identification and the Russian revolution from the perspective of psychological history via a cultural-historical approach. As a result, in Vygotsky’s cultural-historical theory, a person’s ability to experience appears as a dynamic unit in which the effect and intellect combine emotional and cognitive aspects, acting as an indicator and significant personality characteristic. In conclusion, the last feature perceived today as an absolute anachronism, at that time nevertheless reflected not only the way of communication (or rather, anti-communication) but also the modernization model of social development as a whole